Mast cell hyperactivity as the factor in the pathogenesis of male infertility - N. G. Kulchenko (Исследования и практика в медицине)
The proportion of men with impaired sperm fertility is increasing every year, which is one of the factors in the decline in fertility and is becoming both a medical and social problem. Modern diagnostic methods make it possible to recognize many factors of male infertility: genetic, endocrine, infectious, extra-genital, etc. However, despite all modern biomedical advances, 1/3 of patients remain with an unrecognized cause (idiopathic) of male infertility. At the same time, we must not forget that most patients from this category do not want to resort to assisted reproductive technologies to realize paternity, and they strive to achieve pregnancy in a natural way. Therefore, the search for the causes of male infertility remains an urgent issue in modern urology field. This article reviews the literature on the role of mast cells in the formation of fibrosis in tissues, including the testis. Mast cells affect the proliferation, functioning and phenotype of fibroblasts put under hypoxic conditions. Fibroblast activation enhances collagen fibrillogenesis. Studies by Russian and foreign scientists have shown that with sperm pathology, the number of mast cells in the connective tissue of the testicle increases sharply. Against the background of an increase in the number of mast cells in the interstitium of the testis, fibrosis of the wall of the convoluted seminiferous tubules increases. Moreover, in severe spermatogenesis disorders (Sertoli cell-only syndrome, Germ cell aplasia), mast cells were found both in the peritubular space and in the lumen of the convoluted seminiferous tubules. Most infertile men have significant amounts of significant amounts of mast cells in their ejaculate. There are sporadic data on the negative correlation between the presence of mast cells in seminal plasma and the concentration and motility of spermatozoa. Conclusion. The negative effect of mast cells on spermatogenesis remains unknown to the end. Mast cells have a high ability to migrate to connective tissue, which levels increase during inflammation, and the production of many mediators, proteases and histamine, cytokines, which can be both a trigger in the formation of sperm pathology and the cause of the formation of fibrosis in the testicle.